Ultrasound-Assisted Synthesis of Activated Carbon from Palm and Candlenut Shells for Efficient Nickel Ion Adsorption - Andi Asdiana Irma Sari Yusuf; Yuli Amdia Riski; Herlina Rahim; Ibtisamatul Aminah; Nur An-nisa Putry Mangarengi; Sariwahyuni; Idi Amin; Syardah Ugra Al Adawiyah (University of Jember, 2025)
An excessive concentration of nickel in aquatic systems poses significant risks to the environment and living organisms, particularly when it exceeds established environmental quality standards. Conventional treatment techniques such as chemical precipitation, ion exchange, and membrane filtration are often limited by high operational costs, complex maintenance, and the generation of secondary sludge. Biomass-derived activated carbon has emerged as a sustainable and cost-effective adsorbent with notable adsorption potential. However, studies exploring hybrid biomass sources for activated carbon production remain scarce. This study investigates the feasibility of using ultrasonically activated carbon derived from a 50:50 blend of palm and candlenut shells for the adsorption of Ni²⁺ from aqueous solutions. The biomass underwent carbonization followed by ultrasonic activation at 48 kHz and was subsequently subjected to comprehensive physicochemical characterization and batch adsorption experiments. The optimized hybrid adsorbent exhibited the highest fixed carbon content (84.68%) and iodine number (374.36 mg/g). Adsorption tests revealed a Ni²⁺ removal efficiency of 77.33% within 30 minutes. Fourier Transform Infrared (FTIR) analysis showed the presence of main functional groups (-OH, C=O, C=C) that can bind metal ions. This emphasized the ultrasonic activation potential as an eco-friendly process for producing high-quality activated carbon, contributing to water treatment and aligning with circular economy principles.